PENDIDIKAN BERKEUNGGULAN INSAN - Gunawan, Gunawan (Jurnal Cakrawala Pendidikan, 2016)
In existentialism, the existence of one thing is always in the company ofone or more other things. Thus, to give a correct idea or to avoid misunderstandings of the use of the predicate unggul as in terms like bibit unggul, sekolah unggulan, produk unggulan pendidikan, and others, it is morally imperative for the users of such terms to provide the terms with their contexts to determine whether unggul means ’prime’, ’superior’, ’competitive’, or any other. Instances of such contexts can be of appearance or performance, of a long or short term, of current objectives or future goals, of individuals or the community, of individual or social needs, of national or international needs, of inclusive or exclusive purposes, and others. Even now, the writer is still of the belief that the usage of those aforementioned terms in the field of education in Indonesia is still more as jargon rather than basic concepts. Indeed very rarely or even never does the public, particularly those who are very much concerned with the development of education in Indonesia, to get a thorough explanation of those terms mentioned. This article tries to build a kind of "second opinion" as a balance to the existence ofthat jargon menti